(untitled) (Bangladesh Journal of Medical Science, 2023)
Background: Low power laser therapy or low-level laser therapy (LLLT) is relatively novel and has demonstrated tremendous advantages in dentistry which includes reduction in post-surgical pain as well as swelling and also accelerates wound healing and helps in bone regeneration etc. Objective: This systematic review aimed to find out whether low-level laser therapy promotes tooth extraction wound healing. Materials and Methods: Literature was searched from January 2010 till 31 December 2020 using PubMed, Scopus, and Web of science. Further findings were done from gray literature google scholar, and Research Gate using Low-level laser therapy, photobiomodulation, wound healing, extraction socket healing, cold laser, biostimulation, low-level laser irradiation, and phototherapy. Any article that reported effects of low-level laser therapy on wound healing was included. 19 studies fulfilled the criteria and were included for this systematic review. Quality assessment was done for each article using Joanna Briggs Institute (JBI) checklist for analytical cross-sectional studies. Results and Discussion: Throughout the search, approximately 22,808 relevant articles were found. Out of which 50 articles fulfilled the selection criteria. 31 articles were excluded because that did not fulfill inclusion criteria. 19 articles were included for this systematic review that compared the effects of low level-laser therapy on wound healing after extraction of a tooth. Conclusion: Overall, this systematic review concluded that low-level laser therapy enhanced the process of wound healing after extraction of teeth but most of the research was conducted on animals. Further research is needed to investigate the biostimulatory effects of low-level irradiation on wound healing after extraction of a tooth Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 585-597